Microrna-135A-5P promotes proliferation and metastasis of hepatocelluar carcinoma cells via down-regulation of FOXO1 - Tian Zhang; Lingling Guan; Xiaomeng Xie; Lixing Guo; Dongjing Ni (Brazilian Journal of Pharmaceutical Sciences)
Abstract Numerous studies have focused on microRNAs (miRNAs) in hepatocellular carcinoma (HCC). However, the specific role of miR-135a-5p in HCC has remained unclear. Thus, this study aimed to elucidate the role and mechanisms of action of miR-135a-5p in HCC. Transfected Huh-7 HCC cells were subjected to cell proliferation, apoptosis, migration, and invasion assays to investigate the role of miR-135a-5p and FOXO1 in modulating cellular functions. Additionally, tumor xenografts from nude mice were utilized in vivo to validate the in vitro findings. Downregulation of miR-135a-5p or upregulation of FOXO1 inhibited cell proliferation and metastasis of Huh-7 cells while promoting apoptosis. Conversely, upregulation of miR-135a-5p induced proliferation and metastasis of Huh-7 cells while suppressing apoptosis. Furthermore, FOXO1 was identified as a direct target of miR-135a-5p. Notably, downregulation of miR-135a-5p or upregulation of FOXO1 suppressed tumor growth in Huh-7 cells. Inhibition of miR-135a-5p impeded HCC cell proliferation and metastasis by upregulating FOXO1 expression.